Descriptive Metaphysics, Natural Language Metaphysics, Sapir-Whorf, and All That Stuff: Evidence from the Mass-Count Distinction - Francis Jeffry Pelletier (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
Strawson (1959) described ‘descriptive metaphysics’, Bach (1986a) described ‘natural language metaphysics’, Sapir (1929) and Whorf (1940a,b, 1941) describe, well, Sapir-Whorﬁanism. And there are other views concerning the relation between correct semantic analysis of linguistic phenomena and the “reality” that is supposed to be thereby described. I think some considerations from the analyses of the mass-count distinction can shed some light on that very dark topic.